Efeitos do método pilates na dor, força muscular e autopercepção de saúde de idosos da comunidade - Rahhal, Karine Demartini (2021)
Human aging is inexorable and universal; takes place around the world, and in an accelerated way in Brazil. This phenomenon changes society and the individual; in the individual dimension, there is a reduction in physiological reserve, intrinsic capacity, and ability to respond to stressors. These changes are primarily mediated by changes in biological, psychological, spiritual and social aspects. To minimize the impact of these changes and allow for successful aging, it is essential to develop in-depth scientific knowledge about assertive, low-cost and high-adherence therapeutic strategies. Several studies point to bodily activities as the gold standard for this purpose, and among the various possibilities of bodily activities is the pilates method, a methodology that aims to balance body and mind developed in 1920, and despite its evolution over the decades still it lacks further scientific evidence to confirm its benefits. Thus, this dissertation systematically investigated publications in the literature on the Pilates method in the elderly population, with the aim of verifying its effects on the outcomes: pain, muscle strength and self-perceived health. The results achieved were described in three scientific productions; Production I found the scarcity of randomized clinical trials, with populations exclusively of elderly people, and with validated instruments to assess the effects of the method on pain, despite the few primary studies included, it was possible to verify the method's success in reducing low back pain in elderly women. Production II presented qualitative data that indicate the increase in muscle strength of hip flexors and extensors. And quantitative data that demonstrated increased muscle strength of knee flexors and extensors. Finally, production III showed the implications of the method on self-perceived health, mediated by variations in the SF-36 domains of mental health and general health. The results surveyed suggest a benefit of the method in reducing pain complaints, increasing muscle strength and expanding self perception of health among the elderly in the community. However, future experimental research is needed to deepen the present findings, with the inclusion of a broad and homogeneous elderly population, standardization of measurement instruments and reproducible intervention protocols.